2019
DOI: 10.1371/journal.pone.0220463
|View full text |Cite
|
Sign up to set email alerts
|

The feline cutaneous and oral microbiota are influenced by breed and environment

Abstract: Previous research revealed the feline skin bacterial microbiota to be site-specific and the fungal microbiota to be individual-specific. The effect of other factors, such as genotype and environment, have not yet been studied in cats, but have been shown to be potentially important in shaping the cutaneous microbiota of other animals. Therefore, the objectives of this study were to evaluate the effect of these factors on the bacterial and fungal microbiota of feline skin and oral cavity. The influence of genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 75 publications
4
50
0
Order By: Relevance
“…For example, in cats without periodontal disease, studies have shown that the most common phyla sampled have consistently been Bacteroidetes, Firmicutes, and Proteobacteria (Sturgeon et al, 2014;Dewhirst et al, 2015;Harris et al, 2015;Adler et al, 2016;Older et al, 2019), while in those with periodontitis and/or gingivitis, a high degree of variation in pathogenic bacteria has been reported, with little similarity across studies (Perez-Salcedo et al, 2013;Harris et al, 2015;Whyte et al, 2017).…”
Section: Oral Healthmentioning
confidence: 99%
“…For example, in cats without periodontal disease, studies have shown that the most common phyla sampled have consistently been Bacteroidetes, Firmicutes, and Proteobacteria (Sturgeon et al, 2014;Dewhirst et al, 2015;Harris et al, 2015;Adler et al, 2016;Older et al, 2019), while in those with periodontitis and/or gingivitis, a high degree of variation in pathogenic bacteria has been reported, with little similarity across studies (Perez-Salcedo et al, 2013;Harris et al, 2015;Whyte et al, 2017).…”
Section: Oral Healthmentioning
confidence: 99%
“…Recently, methods based on next generation sequencing (NGS) have allowed a better characterization of the complex microbial communities occurring on animal skin and made it possible to detect Malassezia species that would otherwise be missed using culture-based methods (Meason-Smith et al, 2017Korbelik et al, 2018;Older et al, 2019). Meason-Smith et al reported that the cutaneous mycobiota in dogs was influenced by various factors including environmental exposure, cohabitation with other pets and skin health status (Meason-Smith et al, 2015).…”
Section: Ecology Of Malassezia Yeasts In Dogs and Cats: Complementarymentioning
confidence: 99%
“…When samples from healthy and allergic cats were collected, the most abundant fungal sequences were identified as filamentous contaminants from the environment and not Malassezia yeasts, which were identified in 30 and 21% of healthy and allergic cat samples, but rarely accounted for more than 1% of the relative fungal abundance (Meason-Smith et al, 2017). The objectives of the recent study from Older et al were to evaluate how genotype and environment can influence the bacterial and fungal microbiota of feline skin (Older et al, 2019). Using NGS and Malassezia qPCR, they demonstrated that M. restricta and M. globosa were the most prevalent Malassezia species.…”
Section: Ecology Of Malassezia Yeasts In Dogs and Cats: Complementarymentioning
confidence: 99%
See 2 more Smart Citations